Prolonged neurotoxicity in a lymphoma patient after CD19‐directed CAR T‐cell therapy: A case report and brief review of the literature. Issue 3 (1st November 2020) - Greenbaum, Uri; Ramdial, Jeremy L.; Olson, Amanda; Nieto, Yago; Strati, Paolo; Ahmed, Sairah; Neelapu, Sattva S.; Tummala, Sudhakar; Chi, Linda; Shpall, Elizabeth J.; Kebriaei, Partow
Abstract: As the field of cancer therapeutics moves increasingly toward targeted and cellular therapies, this evolution comes with new hurdles. Toxicity of these therapies can result in serious adverse events that can become life‐threatening. In particular, cytokine release syndrome (CRS) and immune effector cell‐associated neurotoxicity syndrome (ICANS) are now the most common adverse effects resulting from chimeric antigen receptor (CAR) T‐cell therapy. Furthermore, CAR T cells are reported to cause hyperactivation of macrophages, which in extreme cases results in hemophagocytic lymphohistiocytosis (HLH). These toxic effects result from cytokines released as a direct effect of the therapy. Physicians are evaluating inflammatory markers to monitor longitudinally cytokine stimulation and immune activation after therapy, which can help predict and gauge the severity of the cytokine storm. Prompt recognition of toxic effects and rapid intervention are essential in the management of patients receiving CAR T‐cell therapy. Despite intervention, some patients still experience severe and prolonged ICANS. Herein we present a patient with lymphoma who developed prolonged ICANS and reviewed the literature on neurotoxicity and macrophage activation resulting from CD19‐directed CAR T‐cell therapy.